2016
DOI: 10.1016/j.cellsig.2016.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Common pathways regulate Type III TGFβ receptor-dependent cell invasion in epicardial and endocardial cells

Abstract: Epithelial-Mesenchymal Transformation (EMT) and the subsequent invasion of epicardial and endocardial cells during cardiac development is critical to the development of the coronary vessels and heart valves. The transformed cells give rise to cardiac fibroblasts and vascular smooth muscle cells or valvular interstitial cells, respectively. The Type III Transforming Growth Factor β (TGFβR3) receptor regulates EMT and cell invasion in both cell types, but the signaling mechanisms downstream of TGFβR3 are not wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 47 publications
(94 reference statements)
2
15
0
Order By: Relevance
“…Depletion of Tgfbr3 has led to mice embryonic lethal due to failed coronary vasculogenesis . Additional phenotypes associated with decreased proliferation and invasion of Tgfbr3 ‐knockout (KO) epicardial cells in vitro have been observed . In zebrafish, knockdown of Tgfbr3 by injection of antisense morpholinos lead to impaired angiogenesis in morphant embryos .…”
Section: Discussionmentioning
confidence: 99%
“…Depletion of Tgfbr3 has led to mice embryonic lethal due to failed coronary vasculogenesis . Additional phenotypes associated with decreased proliferation and invasion of Tgfbr3 ‐knockout (KO) epicardial cells in vitro have been observed . In zebrafish, knockdown of Tgfbr3 by injection of antisense morpholinos lead to impaired angiogenesis in morphant embryos .…”
Section: Discussionmentioning
confidence: 99%
“…An excellent recent example is a study by Clark et al, 2016 that involved several parallel approaches that would be challenging in an in vivo setting (Clark et al, 2016). Cells from genetically altered mice can be cultured on collagen gels to test hypotheses involving the function of specific genes in EMT.…”
Section: Current Use Of the Collagen Gel In Emt Researchmentioning
confidence: 99%
“…Cells from genetically altered mice can be cultured on collagen gels to test hypotheses involving the function of specific genes in EMT. An excellent recent example is a study by Clark et al, 2016 that involved several parallel approaches that would be challenging in an in vivo setting (Clark et al, 2016). Using a combination of pharmacologic and genetic techniques they found that in epicardial and endocardial cells of the heart NF-kB acts downstream of TGFb receptor III (Tgfbr3) to induce EMT.…”
Section: Current Use Of the Collagen Gel In Emt Researchmentioning
confidence: 99%
“…Thus, it was of interest that two TNF receptor superfamilies ("SF") showed increased expression in ALS MN's: TNFRSF1A (ALS/CTL = 3.0) and TNFRSF21 (ALS/CTL = 2.0). The latter is associated with NFkβ signaling, which has been shown to mediate EMT of non-neoplastic cardiac cells [53]. If EMT is occurring in adult ALS motor neurons, this would represent a new paradigm, amenable to inhibition, such as has been demonstrated with rapamycin treatment of cervical carcinoma cells [54] and curcumin treatment of human kidney tubular epithelial cells [55].…”
Section: Limitations Of Gene Expressionmentioning
confidence: 99%
“…In terms of additional investigations, it might be worthwhile to pursue the possibility that the "prolonged autophagic death" described by Martin [49] and increased autophagy markers in sporadic ALS MN's described by Sasaki [45] might arise as a result of oxidative stress-driven autophagy [48] through activation of epithelial-mesenchymal transition (EMT) of motor neurons. EMT is not known to occur normally in non-malignant tissues except during developmental neuronal polarization and migration [50], amniotic membrane rupture [51], organ fibrosis [52] and cardiac cells in culture [53]. EMT can be stimulated by a variety of factors, including TNF-α.…”
Section: Limitations Of Gene Expressionmentioning
confidence: 99%